Comparison of Anesthetic Methods and Postoperative Analgesic Requirement in Lower Extremity Orthopedic Surgery - Suwannarurk, Lakkana (Journal of Health Science of Thailand, 2018)
Lower extremity surgery is common in orthopedics intervention. This prospective, outcome randomized, controlled study was designed to evaluate the postoperative analgesic requirement within 24 hours among various methods of anesthesia. In all, 150 patients were randomized to receive either general anesthesia (GA; group I), spinal anesthesia (SA; group II) or spinal with morphine anesthesia (SA & MO; group III). ASA status of all subjects was between I, II and III. The Visual Analog Score (VAS) and analgesic requirements in group III patients were statistically lower than those of the others (p<0.05). Consequently, SA&MO had significantly more pruritus than the others (p<0.05). In conclusion, spinal anesthesia with morphine seems to be a more effective alternative than GA and SA in lower extremity orthopedics surgery.